Social Elements that Causing Trauma to The Characters in The Nickel Boys (2019) by Colson Whitehead - Sisla Rahmi; Delvi Wahyuni (Universitas Negeri Padang, 2023)
This thesis is used psychoanalysis theory from the novel entitled The Nickel Boys by Colson Whitehead (2019) this thesis focus on what factors or elements causes trauma to the characters in The Nickel Boys (2019) by Colson Whitehead. The analysis is used psychoanalysis theory by Sigmund Freud. This thesis also find the defense mechanism the characters used to deal with trauma caused by social elements.